ANALISIS SISTEM KARUN DALAM HUBUNGAN KERJASAMA ANTARA PEMILIK KEBUN KELAPA DENGAN PEKERJA DALAM PERSPEKTIF EKONOMI ISLAM DI DESA PULAU PALAS KECAMATAN TEMBILAHAN HULU - Hendra Refi Ardiansyah; Eja Armaz Hardi; Dessy Anggraini (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Musaqah is a form of cooperation between plantation owners and sharecroppers with the aim of ensuring that the plantation is cared for so that it provides maximum results. The aim of this thesis is to determine the application of the coconut plantation musaqah system between land owners and workers from an Islamic economic perspective in Pulau Palas Village, Tembilahan Hulu District. This thesis uses a qualitative approach, the informants in this research are plantation owners, workers and coconut buyers as well as village officials using data collection methods through observation, interviews and documentation. The results of this research show that in practice this musaqah contract collaboration has gone quite well, but there are still sharecroppers who have committed fraud by secretly selling rubber latex products. According to an Islamic economic perspective, the implementation of al-musaqah profit sharing from coconut plantations carried out by the community in Pulau Palas Village, Tembilahan Hulu District has a good aim for the survival of coconut farmers, but in its implementation it is not in accordance with the provisions of Islamic law in cooperation, because besides often There are disputes in the distribution of profits and not all coconut owners and workers set a time limit for when the implementation of al-musaqah profit sharing ends. When carrying out the contract, they do not determine the nature, type and kind, all of which are conditions and pillars in al-musaqah profit sharing.